1982
DOI: 10.1007/bf03007130
|View full text |Cite
|
Sign up to set email alerts
|

Systemic air embolism following manual lung inflation

Abstract: A case is reported in which a young man undergoing exploratory thoracotomy following a gunshot wound had a cardiac arrest during reinflation of the collapsed lung. Systemic air embolism was suspected as the cause. Subsequent neurological examination and C.T. scan demonstrated a lesion ascribable to this. Discontinuation of nitrous oxide, aspiration of left heart chambers and a head-down position are recommended as immediate treatment if this diagnosis is made. In cases with piercing lung trauma high inflation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Most reported cases of SAE associated with isolated penetrating lung injury have a fatal outcome. 1,8,9,[11][12][13][14][15][16][17][18][19][20] In one series of 61 patients with documented SAE, 15 patients had blunt trauma and 46 patients had penetrating trauma. 9 The blunt group had a mortality rate of 80%, and the penetrating group rate was 48%.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Most reported cases of SAE associated with isolated penetrating lung injury have a fatal outcome. 1,8,9,[11][12][13][14][15][16][17][18][19][20] In one series of 61 patients with documented SAE, 15 patients had blunt trauma and 46 patients had penetrating trauma. 9 The blunt group had a mortality rate of 80%, and the penetrating group rate was 48%.…”
mentioning
confidence: 99%
“…Indeed, of the 107 or so published cases of SAE, 8,9,[11][12][13][14][15][16][17][18][19][20] no effort to limit airway pressures or to selectively ventilate the uninjured lung (in unilateral lung trauma) was mentioned except in those described by Saada et al 11 Using transesophageal echocardiography, these authors demonstrated (1) the cessation of intracardiac air emboli in between positive pressure cycles, and (2) the decrease of emboli when ventilatory pressures and volumes were decreased. 11 Based on intuition and the experience of Saada et al, 11 I believe it is appropriate to re-examine the heretofore-neglected airway and breathing components of the resuscitation of patients who are at risk or suspected of having SAE.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…More invasive treatment has been attempted with variable success. Direct ventricular or central venous catheter aspiration may produce clinical improvement 1,28,29 . External cardiac massage is of little benefit in patients with chest trauma, and may cause additional injury.…”
Section: Discussionmentioning
confidence: 99%